Assessment of nanoparticle loading and dispersion in polymeric materials using optical wavefront correlation. (July 2015) - Koukoulas, T.; Broughton, W.R.; Woolliams, P.
Abstract: Small concentrations (≤5 wt. %) of nanoparticles in polymeric materials can potentially result in improvements in material properties and functionality. However, poor or non-uniform particle dispersion resulting in clustering (agglomeration) in polymer nanocomposites (PNCs) limits the potential for property enhancement. Achieving good dispersion is considered essential for large-scale production and commercialization of PNCs. New and effective measurement techniques capable of quantitatively characterizing particle loading and dispersion would significantly contribute towards understanding and optimizing the material performance of PNCs and, consequently, play a pivotal role in product development. This paper presents the results of a study using a static light scattering technique, optical wavefront correlation (OWC), for discriminating between different particle loadings and levels of dispersion. The technique has been applied to a range of PNCs, including epoxy resins reinforced with nanoclay platelets or silica microspheres, and zinc oxide and lithium aluminate reinforced polypropylene.